CROSS-LINGUISTIC INFLUENCES OF MALAY THROUGH CARTOONS ON INDONESIAN CHILDREN’S LANGUAGE USE IN THE HOME DOMAIN - Aziz, Zulfadli A.; Yusuf, Yunisrina Qismullah; Nasir, Chairina; Masyithah, Claudia (Indonesian Journal of Applied Linguistics, 2017)
The Malay cartoons that air on Indonesian television channels are now popular among children in Indonesia. The shows Upin Ipin, Boboboi, and Pada Zaman Dahulu are especially popular with Acehnese children. Initial observations found that these cartoons have played a great role in the increased use of contemporary Malay in their Indonesian. Thus, this study discusses the cross-linguistic influences of Malay from cartoons in Indonesian children’s language use in the home domain. Data were collected through recordings and field notes. Some steps based on the framework by Lacey and Luff (2007) were taken to analyze the data. The results were transcribed and sifted to distinguish the significant data. The recording and its transcription were then re-checked. The last step was categorizing the data into cross-linguistic influences based on Ringbom (1987). These influences include borrowing, hybrids, phonetic influence, and relexification. The results showed the presence of only two aspects of cross-linguistic influences: borrowing and phonetic influences. Borrowing was the most frequent aspect, followed by phonetic influence. Relexification and hybrid did not appear in the data. Nevertheless, there were other cross-linguistic aspects that were found in the data, including intonation, parenthetic remark, and interjection. In the broad-spectrum, the initial mimic on the Malay cartoon characters has expanded to employment in the language use of the children while speaking Indonesian. This study is expected to contribute in some ways or another towards the development of sociolinguistics, especially in cross-linguistic influence in children’s language use. Indonesia and Malaysia are neighboring countries, and language contact between the two countries is inevitable and evident. Hence, the study on the influences can benefit sociolinguistics, especially when investigating language change in the future.